The Parallax Memory. Notes on the Solidarity, Solidarity… collection - Klejsa, Konrad (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
The paper focuses on Solidarity, Solidarity…, a collective project made in 2005 to celebrate the 25th anniversary of the worker’s movement. Thirteen novelettas demonstrate various approaches towards the so-called “Polish August” of 1980, ranging from “comemorational”, praising the leaders of the movement, to critical, stimulating new interpretations of Polish history. The theoretical foundation of the analysis is built upon Deleuze’s theory of “time-image”. Although it may be argued that Deleuze’s work deals primarily with film style and the historically shifting aesthetics of the cinema, it is also justifiable to state that (if treated metaphorically) the Deleuzean “Time-Image” is based on the concept of a journey into the realms of the Forgotten, whereas its spectator is forced to rework his position in the field of history. In the paper, special attention is given to episodes which deal with the nature of history in a specific way. In Jacek Bromski’s short story, a former dissident asks his oppressor for a loan, leading to a replay of his interrogation. In Robert Glinski’s short story, Japanese tourists take pictures of the deserted Gdynia shipyard where Solidarity began. In Juliusz Machulski’s novelette, Solidarity never happened, so the director ponders making a movie about the heroic Battle of Lenino. These short films trace the inability to cope with the heritage of Solidarity, which became a deserted space in public debate during the course of its demolition and reconstruction.

Artykuł koncentruje się na filmie Solidarność, Solidarność…, zbiorowym projekcie przeprowadzonym w 2005 roku w celu uczczenia 25 rocznicy związku robotników.  Każda z trzynastu etiud manifestuje inne podejście do tak zwanego „polskiego sierpnia 1980”, od „upamiętniających”, chwalących przywódców ruchu, po krytyczne, stymulujące nowe interpretacje historii Polski. Teoretyczne podłoże analizy opiera się na koncepcji „kina-czasu” Gillesa Deleuza. Mimo możliwych obiekcji, że dzieło Deleuza zajmuje się przede wszystkim filmowym stylem i historycznie zmienną estetyką kina, uzasadnione wydaje się twierdzenie, że Deleuzyjska koncepcja „kina-czasu” (jeśli potraktować ją metaforycznie) bazuje na wyobrażeniu o podróży w realia Zapomnianego, podczas gdy widz zmuszony jest do przepracowania swojej pozycji na polu historii. Artykuł skupia uwagę przede wszystkim na tych etiudach, które w specyficzny sposób podejmują problem istoty historii. W noweli Jacka Bromskiego, były dysydent prosi swojego prześladowcę o pożyczkę, co prowadzi do powtórzenia procesu interrogacji. W etiudzie Roberta Glińskiego, japońscy turyści fotografują porzucone tereny gdańskiej stoczni, gdzie powstała Solidarność. W noweli Juliusza Machulskiego, Solidarność nigdy się nie wydarzyła, w związku z czym reżyser zastanawia się nad zrobieniem filmu o heroicznej bitwie pod Lenino. Te krótkometrażowe filmy diagnozują niezdolność do poradzenia sobie z wielkim dziedzictwem Solidarności, które stało się spustoszoną przestrzenią debaty publicznej w procesie ciągłego niszczenia i rekonstruowania.
Pamięć i paralaksa. Uwagi na temat Solidarność, Solidarność…
Konrad Klejsa, Katedra Mediów i Kultury Audiowizualnej Uniwersytetu Łódzkiego, Pamięć i paralaksa. Uwagi na temat Solidarność, Solidarność… , The Parallax Memory. Notes on the Solidarity, Solidarity… collection, „Images” 2012, vol. XI: (Re)imagining the Past, red. A. Mrozewicz i J. Czaja, nr 20, s. 23-35, ISSN 1731-450x, język: angielski
Keywords: film and memory; cinematic images of political movements; Deleuze and cinema; Solidarność, Solidarność; film i pamięć; filmowe obrazy ruchów politycznych; Deleuze i kino